Şu’ūbatu al-Kitābah al-Akādīmiyah Ladā Țulāb al-Lugah al-‘Arabiyah - Renti Yasmar (KURAS Institute, 2024)
This small survey examined the challenges of academic writing for Arabic language teaching students, Department of Arabic Language Teaching at Curup State Islamic University. This questionnaire aims to answer two questions: What academic writing difficulties do Arabic Language Education (PBA) students face, and what factors can cause these difficulties?. The subjects of this study were 20 Curup State Islamic University students in the program of Arabic Education. Two questionnaires were used to collect data for this study. Questionnaire 1 contains closed questions. Two people were asked to fill out similar questionnaires to support the quantitative data collected from the first questionnaire, most of which contained open-ended questions. The results showed that subjects tend to have similar difficulties in academic writing regardless of their previous educational context. The most common difficulties are related to the use of language and coherence. Other difficulties with writing are associated with own results and finding relevant topics and sources, including references and quotes. Another conclusion that can be drawn is that various factors can contribute to these difficulties. The main factors are lack of experience and prior knowledge of academic writing conventions and poor academic writing learning process for students.